Elementary Students’ Logical-Thinking Ability and Its Relationship with Gender - Henni Riyanti; Putri Dewi Nurhasana (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Logical-thinking ability is one of the 21st-century competencies that plays an important role in an individual’s ability to be responsive in acting and taking decisions to solve societal problems. However logical-thinking ability can be different from one to another due to several factors, one of that is gender. This research, therefore, was aimed at identifying the relationship between elementary school students’ logical-thinking ability and gender. 149 students from 5 different elementary schools in Surakarta City, Indonesia, were involved in this research. The research subjects were taken by random sampling technique. The data were tested using the validity and reliability tests of logical thinking, which were then analyzed using a quantitative descriptive technique on SPSS 22 software with the Pearson Correlation test. The results showed that there was a significant relationship between logical-thinking ability and gender seen from the correlation value of the Pearson Correlation test of 0.210 and Sig. of 0.01 0.05. Hence, the logical-thinking ability is strongly connected with gender. The result showed that the female students’ logical-thinking ability was better than male students. These results can then be taken into consideration for educators to design appropriate learning so that educators can develop logical thinking skills for both male and female students.